Tratamento de sementes de feijão com tiametoxam - Almeida, Andréia da Silva (2012)
Insecticides and fungicides are often studied to their efficiency in controlling pests and diseases, however can cause physiological effects little known that can affect crop growth. Thiamethoxan is a systemic insecticide from the neonicotinoid group, nitroguanidine family, which acts on nicotinic acetylcholine receptor of insects, damaging their nervous system, leading them to death. This insecticide, that is widely used for controlling pests and sucking insects, has bioactivator effect, since even in the absence of pests, promotes an increase in vigor and development in treated plants. It is believed that the effects of thiamethoxan in plants are indirect, because it acts in the genes expression responsible for metabolic enzymes activation and synthesis, related to plant growth, by modifying amino acids and plant hormones precursors production. There is a number of studies with thiamethoxan in the way to determine the effects on metabolism and development of plants, but the results are not clear, showing strong interaction between cultivars, stress conditions and nutrient availability. Due to the wide use of the insecticide thiamethoxan in Brazilian agriculture, the study of this insecticide in order to know the metabolism changes in the plants, brings a great importance in the collection of knowledge to the agronomic and biological literature. In this context, the objectives were: to determine the effect of physiological performance of bean seeds treated with thiamethoxam.